Mesoscale Models From Micro-Physics to Macro-Interpretation - Mesarovic, Sinisa; Forest, Samuel; Zbib, Hussein; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book helps to answer the following questions: How far have the understanding and mesoscale modeling advanced in recent decades, what are the key open questions that require further research and what are the mathematical and physical requirements for a mesoscale model intended to provide either insight or a predictive engineering tool? It is addressed to young researchers including doctoral students, postdocs and early career faculty.
Physical foundations of mescoscale continua -- Multiscale dislocation-based plasticity -- Statistical theory of dislocation -- Granular materials: micromechanical approaches of model systems -- Multiscale modeling of interfaces, dislocations, and dislocation field plasticity -- Generalized continua and phase-field models. Application to crystal plasticity.
Keywords: Mechanics, Applied; Solids; Soft condensed matter; Building materials; Solid Mechanics; Soft and Granular Matter; Structural Materials